FROM FORMALIZATION OF SHARIA TO ISLAMIC CONSERVATISM: THE POST REFORM OF ISLAMIC MOVEMENT PHENOMENA IN WEST SUMATERA - Zulfadli Zulfadli; Dewi Anggraini; Mhd Fajri (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2020)
This study tries to explain the phenomenon of strengthening of the Islamic conservatism movement, in post Reform of the West Sumatera political context. Soon after the enforcement of the Regional Autonomy Law, various Islamic movements in West Sumatra have massively emerged with various models and issues of the movement. Based on a qualitative approach, wherein the data is collected through in-depth interviews, observations and documentation related to various activities of the Islamic movement in West Sumatra, the results f this show that there has been shifting pattern of its movements; from initially oriented towards the efforts to formalize Islamic sharia, towards Islamic conservatism. The movements, where it's based on religion or custom, which previously were more oriented towards the enforcement of Islamic Sharia legal-formally, later tends to become more socio-cultural movement oriented towards strengthening political identity.